A Blended Biometric Approach Using Matching Score Level Architecture - Divya, K; Narayan, K. G. R; Ramachandran, V; Eswariah, R (International Journal of Computer Sciences and Engineering, 2018)
This paper aims at security authentication for an unmanned surveillance system. The system takes the Face image, impressions of a person’s finger and images of eyes and prepares a database. A blended biometric approach is followed for calculating the weighted average of scores appraised from the three most trivial biometric traits, Face, Eye and Finger impressions. The features are extracted from the pre-processed images of iris, face and finger impressions.The details of a probing image are to be matched with the database we have .the individual details obtained after tallying are sent to the fusion module. This module consists of three major steps i.e., Pre-Processing, Discrete Wavelet Transformation and Image fusion. At the final phase the hidden key Analysis approach is followed to authenticate the subject under investigation.